Faktor-Faktor yang Mempengaruhi Pengetahuan Pasien Hipertensi di Daerah Jeneponto, Provinsi Sulawesi Selatan - Dede - Haryono; Elly - Wahyudin (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Hypertension is a disease that can cause various losses if not appropriately treated. Failure in the treatment of hypertension is caused by a lack of knowledge of patients in their treatment. This study aims to look at the level of expertise of hypertension patients in the Jeneponto area. This study used a cross-sectional method involving 310 patients in the Jeneponto area at the first level of health facilities who had taken hypertension drugs. The questionnaire used was Hypertension Knowledge-Level Scale (HK-LS). The results showed that 23.9% of patients had high knowledge and 76.1% of patients had low knowledge in Jeneponto area. The factors of higher education (p = 0.000, OR = 0.040), secondary education (p = 0.001, OR = 0.299), and occupations such as housewives (p = 0.024, OR = 3.982), retirees (p = 0.021, OR = 10.762) and farmers (p = 0.004, OR = 13.442) were identified as having an influence on knowledge about hypertension. In conclusion, the level of knowledge is influenced by the level of education and occupation in Jeneponto area. Patients with high and middle education have higher knowledge than those with low education and occupations such as housewives, retirees, and farmers who have low knowledge about hypertension. Keywords: Hypertension, Risk factors, Knowledge, Public